Tea sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Although China and India are the leading global tea producers, Kenya is the third largest producer and the largest exporter of black tea. Continuing the trend of the previous five years, in 2012 prices rose, offering Kenyan smallholder producers consistent revenues. However, production costs were also increasing, mainly due to climate-change related adjustments costs. After presenting the main global trends of the tea sector in 2012-13 and the recent developments in some relevant African countries, this Executive Brief highlights some challenges and opportunities for developing Africa’s tea economy in the near future. Besides building strategies to proactively respond to climate change, ACP countries will also need to diversify their trade relations and expand regional trade; develop value-added processing and market diversification strategies; and respond to the strong growth in demand for fair trade and organic tea.